A wind turbine and its robust control using the CRONE method. (November 2020) - Ravasco, Francisco; Melicio, Rui; Batista, Nelson; Valério, Duarte
Abstract: This paper presents the identification, development and simulation of a complex order, third generation CRONE (Commande Robuste d'Ordre Non Entier) controller for a new Darrieus type vertical-axis wind turbine design. A prototype of this wind turbine was developed and tested in a wind tunnel. Data acquired in the tests were used to develop and validate an accurate model. The CRONE control system design methodology was then used to develop a robust controller, which was tested in simulation. Simulations allow for parameter uncertainty in different wind conditions, with and without the presence of turbulence. This control system can be easily implemented using a micro-controller. Highlights: Third generation CRONE controller. Darrieus type vertical-axis wind turbine. Prototype tested in a wind tunnel.